Perspectives on Food & Nutrition Security: The rural-urban continuum - Sharan, Vimlendra (2017)
LAUNCH: 2017 Global Food Policy Report MAR 23, 2017 - 12:15 PM TO 01:45 PM EDT Vimlendra Sharan, Director, Liaison office for North America of the Food and Agriculture Organization of the United Nations (FAO)